Respuestas
Respuesta dada por:
1
Con la ecuación de aceleración constante:
v = vo + at
v: velocidad final ( 54 km/h)
vo: velocidad inicial (5 m/s)
t: tiempo (1 min = 60s)
54 km / h * (1000 m / 1km) * (1 h / 3600 s) = 15 m/s
despejando a:
a = (v - vo) / t
a = (15 - 5) m/s / (60 s)
a = 0,166666 m/s^2
v = vo + at
v: velocidad final ( 54 km/h)
vo: velocidad inicial (5 m/s)
t: tiempo (1 min = 60s)
54 km / h * (1000 m / 1km) * (1 h / 3600 s) = 15 m/s
despejando a:
a = (v - vo) / t
a = (15 - 5) m/s / (60 s)
a = 0,166666 m/s^2
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años